Whole genome sequencing, characterisation and immune-related gene profiling of the Malaysian genotype Vii Newcastle disease virus in chickens - Satharasinghe, Dilan Amila (2016)
Among the different strains of Newcastle disease virus (NDV), genotype VII NDV is the predominant velogenic NDV circulating in South-East Asia including Malaysia causing outbreaks even in well-vaccinated flocks. However, the complete genome sequences of genotype VII Malaysian NDV isolates have never been characterised. Furthermore, the ability of the virus to replicate in different tissues by modulating the host innate immune responses is poorly studied. In this study, we described the application and the establishment of a simple, robust and less resource demanding protocol for whole genome sequencing of NDV by using the Next-Generation Sequencing (NGS) technology on the Illumina MiSeq platform. Five overlapping primer sets were designed to amplify the complete genome of 5 Malaysian NDVs isolated from year 2004 to 2013. Amplified PCR products were subjected to NGS library preparation followed by sequencing in NGS platform. The generated raw sequencing data was imported to genome assembly software to generate consensus by denovo assembly and map to reference. This protocol was able to generate accurate consensus-level full genome sequence for 5 virulent NDV isolates (MB128/04, MB076/05, IBS002/11, IBS005/11 and IBS025/13) obtained from outbreaks that occurred from 2004 to 2013. Intracerebral pathogenicity index and cleavage site motif were assessed to determine the pathoypes and virulence of the NDVs. All the isolates exhibited ICPI values more than 1.5 and demonstrated cleavage site motif 112R/K-R-QR/ K-R↓F117 of F gene which is cleavable by a wide range of proteases, confirming the velogenic nature of the isolates. In order to determine the evolution of the isolated Malaysian NDVs from 2004 to 2013, phylogenetic and pairwise comparisons analysis based on complete genome sequence and all proteins were performed. The phylogenetic analysis of partial fusion (F) gene sequences revealed that all the 5 NDV isolates could be grouped under genotype VII, sub-genotype VIIa, or under Lineage 5a viruses. However, the recent isolates of 2011 (IBS002/2011 and IBS005/2011) have higher genetic distance than NDV isolates of 2004 and 2005 when compared to genotype II vaccine strains. Furthermore, the complete genome sequence of IBS025/13 NDV isolate revealed a natural recombination of genotype II and VII. Further, both phylogenetic and recombination analysis of this isolate confirmed that the nucleoprotein (NP) and the phosphoprotein (P) shared a sequence motif of genotype II, while the rest of the proteins shared genotype VII characters. In addition, the isolate has a genome size of 15,186 nucleotides, which is similar to early genotypes (I-IV) NDVs isolated during the period of 1930 to 1960. The viral copy numbers in infected spleen, lungs and duodenum of Specificpathogen- free (SPF) chickens with different NDV isolates were quantified by quantitative reverse transcriptase real time PCR. In addition, selected immunerelated genes expressions upon infections were assessed by quantitative PCR. Specific-pathogen-free (SPF) chickens infected with the genotype VII isolates MB076/05, IBS002/11 and IBS005/11, as well as the natural recombinant genotype VII, IBS025/13 showed significantly higher viral load (p < 0.05) in spleen, lungs and duodenum compared to respective tissues of SPF chickens infected with genotype VIII isolate, AF2240-I. Furthermore, the natural recombinant genotype VII isolate showed the highest virus copy numbers (p < 0.05) in infected spleen, lungs and duodenum compared to other genotype VII and VIII isolates suggesting that the recombination event may play a role in virus replication and tissue tropism. The ability of genotype VII viruses to produce high viral load is probably due to the ability of the viruses to inhibit the expression of IFN-α and MDA5 activities at an early phase (12 hpi) of infections. A similar trend for IFN-α and MDA5 expressions was also detected in the infected lungs and duodenum at 12 hpi. A more destructive innate immune responses driven by significant up-regulation of IFN-γ by genotype VII isolates MB076/05, IBS002/11, IBS005/11 and IBS025/13 in spleen and lungs were also detected at later stage of infection at 48 hpi compared to genotype VIII AF2240-1 infected spleen and lungs. In conclusion, we have successfully established a protocol based on NGS technology for complete genome sequencing of NDV, which can be used as part of the diagnostic tools in molecular characterisation and evolution of NDV. Characterisation of NDV isolates in this study has successfully determined the virus tropism and their involvement in influencing the production of important cytokines that associated with innate immune responses.